2022
DOI: 10.1038/s41387-022-00198-z
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin level and osteoporosis in Chinese elders with type 2 diabetes mellitus

Abstract: Objectives Several studies demonstrated a positive relationship between hemoglobin level and bone mineral density (BMD). Thus, the association between hemoglobin concentration and osteoporosis in elders with type 2 diabetes mellitus (T2DM) was explored in this study. Methods Totally, 573 elders with T2DM were included in the study. BMD was measured by dual-energy X-ray absorptiometry. Hemoglobin levels were tested. The association between the hemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…Moreover, our study found that higher Hb and Hct levels were protective factors against osteoporosis. This concurs with other studies [ 54 , 55 , 56 ]. In fact, lower levels of Hb and Hct reflect an anemia status, which increases osteoclast activity [ 55 ].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, our study found that higher Hb and Hct levels were protective factors against osteoporosis. This concurs with other studies [ 54 , 55 , 56 ]. In fact, lower levels of Hb and Hct reflect an anemia status, which increases osteoclast activity [ 55 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, there is no consensus on the association between HGB levels, diabetes, and osteoporosis. In the present study, we found that HGB levels were lower in patients with T2DM combined with osteoporosis than in controls, which is partially consistent with the findings of Xiu et al., who found that HGB levels were lower in men with T2DM combined with osteoporosis than in those with normal bone density ( 49 ). At the same time, FN BMD was lower in patients with T2DM combined with anemia than in the control group, which is partially consistent with the findings of Fei et al., who found that patients with low HGB levels combined with T2DM had lower BMD and a higher prevalence of osteoporosis ( 24 ).…”
Section: Discussionsupporting
confidence: 93%
“…Currently, several studies 36–38 have showed a correlation between anemia and reduced BMD. In China, Xiu et al 39 identified that low hemoglobin was associated with the development of osteoporosis in elderly diabetic patients. And in our study of PCa patients, similar results were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several studies [36][37][38] have showed a correlation between anemia and reduced BMD. In China, Xiu et al 39…”
Section: Clinical Utility Of the Nomogram For Predicting Osteoporosismentioning
confidence: 99%